Pay for performance in emerging markets: Insights from China - Du, Jing; Choi, Jin Nam (Journal of International Business Studies, 2010)
With the rapid increase in the application of Western HR practices in emerging markets, it is crucial to investigate how non-Western employees react to Western HR practices such as pay for performance (PFP). We investigate employee reactions to PFP in emerging markets using China as a case. Our multilevel analyses, based on data from 574 engineers in 22 domestic firms and eight foreign firms in China, demonstrated that PFP was positively associated with conscientiousness at the individual level. In contrast, PFP was negatively related to employees’ organizational commitment and interpersonal helping at the organization level. This study suggests that the impact of “culture distance” associated with Western HR practices may be more likely to manifest itself in the collective entity than at the individual level. Employees of domestic firms reported significantly higher levels of performance appraisal satisfaction and justice perceptions than employees of foreign firms, which might explain why PFP was more widely implemented in domestic firms in China. The present results demonstrated that, in addition to the culture distance, the “context distance” between domestic and foreign firms may play a critical role in accruing benefits from PFP, indicating that PFP can be more beneficial to domestic firms than to foreign firms. The present findings provide practical implications for foreign firms operating in emerging markets.